The association of exercise and sedentary behaviours with incident end-stage renal disease: the Southern Community Cohort Study. Issue 8 (30th August 2019) - Pike, Mindy; Taylor, Jacob; Kabagambe, Edmond; Stewart, Thomas G; Robinson-Cohen, Cassianne; Morse, Jennifer; Akwo, Elvis; Abdel-Kader, Khaled; Siew, Edward D; Blot, William J; Ikizler, T Alp; Lipworth, Loren
Abstract : Objective: To examine whether lifestyle factors, including sedentary time and physical activity, could independently contribute to risk of end-stage renal disease (ESRD). Study design: Case-cohort study. Setting: South-eastern USA. Participants: The Southern Community Cohort Study recruited 86 000 black and white participants from 2002 to 2009. We assembled a case cohort of 692 incident ESRD cases and a probability sample of 4113 participants. Predictors: Sedentary time was calculated as hours/day from daily sitting activities. Physical activity was calculated as metabolic equivalent (MET)-hours/day from engagement in light, moderate and vigorous activities. Outcomes: Incident ESRD. Results: At baseline, among the subcohort, mean (SD) age was 52 (8.6) years, and median (25th, 75th centile) estimated glomerular filtration rate (eGFR) was 102.8 (85.9–117.9) mL/min/1.73 m 2 . Medians (25th–75th centile) for sedentary time and physical activity were 8.0 (5.5–12.0) hours/day and 17.2 (8.7–31.9) MET-hours/day, respectively. Median follow-up was 9.4 years. We observed significant interactions between eGFR and both physical activity and sedentary behaviour (p<0.001). The partial effect plot of the association between physical activity and log relative hazard of ESRD suggests that ESRD risk decreases as physical activity increases when eGFR is 90 mL/min/1.73 m 2 . The inverse association is most pronounced at physical activity levels >27 MET-hours/day. High levels of sitting time were associated with increased ESRD risk only among those with reduced kidney function (eGFR ≤30 mL/min/1.73 m 2 ); this association was attenuated after excluding the first 2 years of follow-up. Conclusions: In a population with a high prevalence of chronic kidney disease risk factors such as hypertension and diabetes, physical activity appears to be associated with reduced risk of ESRD among those with preserved kidney function. A positive association between sitting time and ESRD observed among those with advanced kidney disease is likely due to reverse causation.